Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica) - Peña Cantero, Álvaro L. (Zootaxa, 2021)
Peña Cantero, Álvaro L. (2021): Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica). Zootaxa 4966 (3): 321-336, DOI:10.11646/zootaxa.4966.3.4